Bernstein’s theory of the pedagogic device as a frame to study History curriculum reform in South Africa (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
This article rejects on the usefulness of Bernstein’s theory of the pedagogic device to frame a (previously reported) study of history curriculum reform in South Africa: to what extent, and in what ways does the concept of Bernstein’s pedagogic device assist in describing the recontextualising of the history curriculum? The article sets out the reasons for using the pedagogic device inthat study as both a theoretical and methodological frame and a structuring frame which ordered the study and held the various parts together.This perspective locates the study in a field that engages with knowledge from a sociological lens.The article discusses the ways in which Bernstein’s theoretical language supported and strengthened the research, and also shows how it was not specialised enough to engage specifically with the subject of history. Thus it was necessary to weave the field of history education and sociology of knowledge perspective together.
Keywords: Pedagogic device; History curriculum; Sociology of knowledge; Curriculum reform; South Africa